Image-inspired haptic interaction - Zhang, Xingzi; Sourin, Alexei (Computer animation and virtual worlds, 2015)
We add new modality to image‐based visualization by converting ordinary photos into tangible images, which can be then haptically rendered. This is performed by interactive sketching haptic models on the photos so that the models match the image parts, which will become tangible. In contrast to common geometric modelling, we define the haptic models in a three‐dimensional haptic modelling space distorted by the central projection. Analytic FRep functions (variants of implicit functions) are mostly used for defining the haptic models. The tangible images thus created can realistically simulate some actual three‐dimensional scenes by implementing the principle “What You See Is What You Touch” while in fact still be 2D images. Copyright © 2015 John Wiley & Sons, Ltd. We convert ordinary photos into tangible images, which can be then haptically rendered. This is performed interactively by augmenting images with haptic models defined in a 3D haptic modelling space distorted by the central projection. The tangible images thus created can realistically simulate actual 3D scenes by implementing the principle “What You See Is What You Touch” while in fact still be 2D images.